A MoFe nitrogenase-mimicking electrocatalyst for nitrogen fixation with high faradaic efficiency. Issue 37 (21st September 2020) - Liu, Jie; Kong, Wenhan; Jin, Zhaoyong; Han, Yaqian; Sun, Jie; Ma, Liangyu; Niu, Yusheng; Xu, Yuanhong
Abstract : MoFe nitrogenase-mimic electrocatalyst (MoO2 /FeS2 /GA) was proposed for nitrogen fixation, which showed substantially high faradaic efficiency of 37.44%. Abstract : Electrochemical conversion of N2 provides an eco-friendly approach for sustainable ammonia (NH3 ) production, but most electrocatalysts still suffer from low selectivity. Herein, a new three dimensional (3D) graphene aerogel-supported MoO2 and FeS2 nanocomposite (MoO2 /FeS2 /GA) was developed through mimicking the elemental composition and proportion of MoFe nitrogenase. Herein, MoO2 and FeS2 can both act as active sites for nitrogen fixation, while FeS2 plays the role of suppressing the competitive hydrogen evolution activity simultaneously. Moreover, the graphene aerogels can promote the charge transfer and increase the specific surface area of the nanocomposites. Based on the synergistic effects of such a ternary architecture, the electrocatalyst exhibits a high NH3 yield of 40.18 μg h −1 mgcat. −1 and outstanding faradaic efficiency of 37.44% at −0.25 V versus the reversible hydrogen electrode (RHE) in 0.1 M HCl. The selectivity of the as-proposed nanocomposite is superior to those of GA, FeS2 /GA, MoO2 /GA and most previously reported NRR electrocatalysts. Such a bioinspired strategy provides a new avenue to develop more high-efficiency catalysts with controllable activity for the NRR under ambient conditions.